Exchange rate between scientific currencies - An application to the landuse plan of natura 2000 - Vanda Serpa; Vasco Silva; Tomaz Dentinho (European Regional Science Association (ERSA), 2005)
Science is driven by research funds, research funds are associated with decision making, and decision making is attached to valuation. Therefore every scientific paradigm tend to devise its own valuation system. Ecconomists prefer cost benefit analysis where everything can be translated into money. Planners assume values to infinity which lines in a map difining restrictions and enforceable land uses. Ecologists design maps with values for biodiversity. Historians value things according to their age. And engineers enjoy the mathematical control over multicriteria analysis. Anyway, concerning spatial planinng, most of the time there is a line on a map, assumed by polititions and experts and more or less respected by stakeholders. Along this line the total value of alternative uses must be the same. And the total value assumes all the infomation values provided by economists, ecologists, planners, engineers and historians. Because a line has many points it is possible to estimate the exchange rate function between all these different scientific currencies and derive the total economic value of different land uses.
Keywords: 330